Overexpression and Characterization of Organic Solvent-Tolerant Elastase Strain K In Newly Constructed Vectors - Wong, Chee Fah (2010)
Overexpression of an organic solvent tolerant enzyme by means of vector constructionmay facilitate in the synthesis of protein in sufficient amount for characterization study, which include the effect of organic solvents on protein structure. In accomplishing this objective, an extracellular organic solvent tolerant protease of approximately 33 kDa was initially purified to homogeneity from Pseudomonas aeruginosa strain K by ultrafiltration and hydrophobic interaction chromatography with purification fold of 4.37 and a yield of 40.49 %. N-terminal sequencing of the purified protease also demonstrated a well-sequenced 9 amino acid residues, namely -Ala-Glu-Ala-Gly-Gly-Pro-Gly-Gly- Asn- and exhibited high similarities with various strains of P. aeruginosa elastases. Amplification of the Open Reading Frame (ORF) encoding signal peptide, prosequence and mature protein had generated a 1497 bp DNA fragment (HindIII1500PstI) with deduced amino acids of 498 residues. The HindIII1500PstI fragment was successfully cloned to a shuttle vector, pUCP19, and transformed into E. coli strain TOP10 and KRX as well as P. aeruginosa strain PA01 (ATCC 47085) and S5, with detection of significant protein expression. Highest expression level was detected from transformants KRX/pUCP19/HindIII1500PstI of E. coli and PA01/pUCP19/HindIII1500PstI of P. aeruginosa with increase of elastinolytic fold to13.83 and 5.04, respectively, in relative to their controls. New and novel Escherichia-Pseudomonas shuttle expression vectors, pCon2(3),pCon2(3)-Kan and pCon2(3)-Zeo as well as E. coli expression vectors, pCon4 and pCon5, were successfully constructed from pUCP19/HindIII1500PstI, pSS213/PstI1500HindIII, pSTBlue-1 (Novagen, USA) and pPICZαA (Invitrogen, USA). The integration of two series of IPTG inducible promoters in the former three vectors and a tightly regulated promoter, PT7(A1/O4/O3), in the latter two vectors were performed, each to facilitate the overexpression and repression studies of the organic solvent-tolerant elastase strain K. High level of expression was detected in most of the constructed vectors. Several constructs in E. coli and P. aeruginosa namely TOP10/pUCP19/HindIII1500PstI, KRX/pCon2(3), Tuner™ (DE3) pLacI/pUCP19/HindIII1500PstI, S5/pUCP19/HindIII1500PstI and PA01/pCon2(3) exhibited overexpression of elastase strain K. E. coli KRX/pCon2(3) was ultimately selected for subsequent optimization, purification and characterization studies in light of its greatest elastinolytic fold among all the constructs that overexpressed the enzyme. Recombinant elastase strain K overexpressed from E. coli KRX/pCon2(3) was purified to homogeneity by a combination of hydrophobic interaction chromatography and ion exchange chromatography, with a final yield of 48.08 % and an increase of 25.11-fold in specific activity. The purified protein exhibited a homodimer size of 65.39 kDa by SDSPAGE and MALDI-TOF/TOF, a size totally distinct from that typically reported 33 kDa monomer from P. aeruginosa. With half life of 112 and 30 min at 55 and 65 °C,respectively, the enzyme was able to withstand temperatures ranging from 4-60 °C for 30 min with an optimum temperature of 40 °C. pH stability was seen in a broad range of 5.0-1.0 for 30 min in addition to its preference for an acidic environment of 6.0 as the optimal pH for catalysis. The organic solvent stability experiment demonstrated a stability pattern which was completely opposed to the rules of protein stability in organic solvents whereby in this work, activity stability and enhancement were observed in hydrophilic organic solvents of log Po/w ≤ 2.0. The high stability and enhancement of the enzyme in hydrophilic solvents were explained from the view of alteration in secondary structures. The presence of most tested metal ions conferred no effect to the stability of elastase strain K. The enzyme was categorized as a metalloprotease which is partly linked by intramolecular disulfide bonds based on the inhibitory effects observed on metal chelating and reducing agents. The broad substrate specificity in addition to great stability in surfactants and other denaturing agents, displayed by elastase strain K further strengthened the applications of the enzyme as an industrial biocatalyst. The three dimensional structure of elastase strain K was successfully predicted by homology modeling following multiple steps of energy minimization and validation. Regions which deemed essential for catalysis and metal ions binding were also identified from the structure. The disulfide bridges which constituted the tertiary structure of the protein were found to be linked by Cys30-Cys58 and Cys270-Cys297. As a concluding remark, experimental work conducted in this study had indeed highlighted several achievements, novelties and findings including construction of vectors which had led to the understanding of plasmid-host relationship, the overexpression of elastase strain K by constructed vectors, protein dimerization and most importantly, the remarkable stabilityof elastase strain K in hydrophilic organic solvents.